Instructional Interventions in Reading Comprehension Implemented by English Teachers in Public Junior High School in Nueva Vizcaya - Karla Dolore Grapiza; Eilene Bugnay (International Journal of Education, Literacies and Curriculum Studies, 2026)
Persistent gaps in learners’ reading comprehension performance show the need to examine and strengthen instructional interventions in secondary classrooms. This study investigated the reading interventions implemented by teachers, the most frequently practiced strategies, students’ lived experiences of these interventions, the challenges encountered in implementation, and the development of a proposed activity to enhance practice. A mixed-methods design was employed, integrating descriptive quantitative analysis of questionnaire data with qualitative data from open-ended responses, interviews and scanned documents. Data were collected from Key Stage 3 English teachers and purposively selected learners across 47 public secondary schools in Nueva Vizcaya. Findings reveal that teachers implement a comprehensive and integrated set of interventions combining Comprehension Strategy Instruction (CSI), Foundational Reading Skills Instruction (FRSI), and Multicomponent Instruction (MI). Among these, strategies that are practical and immediately responsive to learners’ needs, such as questioning, context clues, inferencing, decoding, vocabulary-building, oral fluency, differentiated instruction, remediation, and the use of localized materials, are most frequently practiced. Students experience these interventions as active and progressive, demonstrating improvements in comprehension, fluency, vocabulary, and confidence, while also showing increased engagement and motivation to read. However, teachers encounter challenges related to time constraints, heavy workload, learner diversity, low motivation, foundational skill gaps, limited resources, inconsistent attendance, lack of parental support, and institutional demands. To sustain and enhance these practices, a division-level activity is proposed to institutionalize effective strategies, strengthen teacher competencies, and promote collaborative approaches to improving reading outcomes.